Evaluation of Knowledge and Awareness of Dentists Towards Cement -Versus Screw-Retained Implant-Supported Prosthesis in Sana'a City, Yemen - Eissa, Nassar Abdo; Al-Kebsi, Abbas Mohammed; Al-Wesabi, Mohammed Ali; Al-Anesi, Waled A. (BEST Journals, 2018)
Implant prostheses can be cement, screw-retained, or both. Implant retention system is typically chosen during treatment planning. The current study assessed the knowledge and awareness of dentists in Sana'a regarding factors affecting decision making between cement versus screw retained implant-supported prosthesis. A questionnaire was distributed to dentists (n = 903) in Sana'a city which showed that 64.4 % of participants they did not provide an implant and 59.7% of them because they were not specialists. 61.2 % of dentists provide a prosthesis for dental implants. There was a statistically significant difference between the dental specialist and GDP about their knowledge level P= 0.03. Dentists being specialists, providing implant treatment and prosthesis for dental implant likely have better knowledge level than others and the differences were found to be statistically significant OR = 3.50; P=0.037, 2.11; P=0.02, 1.83; P=0.03 respectively. The dentists who had ? 5 years of experience likely have better knowledge than the dentists with less than 5 years of expertise but considered non-significant (OR = 1.66, P= 0.063). There is a need to assess the theoretical and practical knowledge of dentists who practice implant in Yemen regularly and to increase their knowledge level regarding the implant-supported prosthesis.